2003
DOI: 10.1128/cdli.10.4.602-611.2003
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Interferon Responses Induced by a Panel of Recombinant and Purified Mycobacterial Antigens in Healthy, Non-Mycobacterium bovisBCG-Vaccinated Malawian Young Adults

Abstract: We have previously shown that young adults living in a rural area of northern Malawi showed greater gamma interferon (IFN-␥) responses to purified protein derivatives (PPD) prepared from environmental mycobacteria than to PPD from Mycobacterium tuberculosis. In order to define the mycobacterial species to which individuals living in a rural African population have been exposed and sensitized, we tested T-cell recognition of recombinant and purified antigens from M. tuberculosis (38 kDa, MPT64, and ESAT-6), M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 79 publications
1
26
0
Order By: Relevance
“…For example, a population in Malawi with no history or scar evidence of prior bCG vaccination or MTB infection showed responsiveness to a variety of mycobacterial antigens and purified protein derivative (PPD) from different NTMs (5,6). In addition, non-MTB-infected and non-bCG-vaccinated individuals respond to MTB-encoded antigens, MTB lysate, and PPD (7,8).…”
mentioning
confidence: 99%
“…For example, a population in Malawi with no history or scar evidence of prior bCG vaccination or MTB infection showed responsiveness to a variety of mycobacterial antigens and purified protein derivative (PPD) from different NTMs (5,6). In addition, non-MTB-infected and non-bCG-vaccinated individuals respond to MTB-encoded antigens, MTB lysate, and PPD (7,8).…”
mentioning
confidence: 99%
“…Studies using several different assays, including lymphoproliferation, gamma interferon (IFN-␥) enzyme-linked immunosorbent assay (ELISA), and IFN-␥ enzyme-linked immunospot (ELISPOT) assay, have shown that they are strong targets of the cellular immune response in animal models, TB patients, and contacts (4,11,24,28,30,35,(37)(38)(39). However, we know very little about the remaining seven RD1 gene products.…”
mentioning
confidence: 99%
“…A kit based on whole-blood production of IFN-␥ detected by enzyme-linked immunosorbent assay (ELISA) is available and has the advantage of relative simplicity, but being based on PPD, it does not ameliorate the poor specificity of skin testing (6). In addition, this test requires 10 ml of blood, a large amount if one considers its application in pediatric practice.We were interested to determine, by the use of a sensitive IFN-␥ ELISA, whether a form of the whole blood stimulation assay that is used by many groups to assay antigen specific responses to RD1 encoded antigens (1,3,7,9,16) could match the performance of the ELISPOT assay. Ethical permission for this study was provided by the Harrow local research ethics committee (Harrow LREC 1646).…”
mentioning
confidence: 99%
“…We were interested to determine, by the use of a sensitive IFN-␥ ELISA, whether a form of the whole blood stimulation assay that is used by many groups to assay antigen specific responses to RD1 encoded antigens (1,3,7,9,16) could match the performance of the ELISPOT assay. Ethical permission for this study was provided by the Harrow local research ethics committee (Harrow LREC 1646).…”
mentioning
confidence: 99%